Imaging mechanical properties of sub-micron ECM in live zebrafish using Brillouin microscopy - Bevilacqua, Carlo; Sánchez-Iranzo, Héctor; Richter, Dmitry; Diz Muñoz, Alba; Prevedel, Robert (Biomedical optics express, 2019)
In this work, we quantify the mechanical properties of the extra-cellular matrix (ECM) in live zebrafish using Brillouin microscopy. Optimization of the imaging conditions and parameters, combined with careful spectral analysis, allows us to resolve the thin ECM and distinguish its Brillouin frequency shift, a proxy for mechanical properties, from the surrounding tissue. High-resolution mechanical mapping further enables the direct measurement of the thickness of the ECM label-free and in-vivo. We find the ECM to be ~500 nm thick, and in very good agreement with electron microscopy quantification. Our results open the door for future studies that aim to investigate the role of ECM mechanics for zebrafish morphogenesis and axis elongation.